New Insights into the Geographic Distribution of Mycobacterium leprae SNP Genotypes Determined for Isolates from Leprosy Cases Diagnosed in Metropolitan France and French Territories. - Florence Reibel; Aurélie Chauffour; Florence Brossier; Vincent Jarlier; Emmanuelle Cambau; Alexandra Aubry (Public Library of Science (PLoS), 2015)
Between 20 and 30 bacteriologically confirmed cases of leprosy are diagnosed each year at the French National Reference Center for mycobacteria. Patients are mainly immigrants from various endemic countries or living in French overseas territories. We aimed at expanding data regarding the geographical distribution of the SNP genotypes of the M. leprae isolates from these patients.Skin biopsies were obtained from 71 leprosy patients diagnosed between January 2009 and December 2013. Data regarding age, sex and place of birth and residence were also collected. Diagnosis of leprosy was confirmed by microscopic detection of acid-fast bacilli and/or amplification by PCR of the M. leprae-specific RLEP region. Single nucleotide polymorphisms (SNP), present in the M. leprae genome at positions 14 676, 1 642 875 and 2 935 685, were determined with an efficiency of 94% (67/71). Almost all patients were from countries other than France where leprosy is still prevalent (n = 31) or from French overseas territories (n = 36) where leprosy is not totally eradicated, while only a minority (n = 4) was born in metropolitan France but have lived in other countries. SNP type 1 was predominant (n = 33), followed by type 3 (n = 17), type 4 (n = 11) and type 2 (n = 6). SNP types were concordant with those previously reported as prevalent in the patients' countries of birth. SNP types found in patients born in countries other than France (Comoros, Haiti, Benin, Congo, Sri Lanka) and French overseas territories (French Polynesia, Mayotte and La Réunion) not covered by previous work correlated well with geographical location and history of human settlements.The phylogenic analysis of M. leprae strains isolated in France strongly suggests that French leprosy cases are caused by SNP types that are (a) concordant with the geographic origin or residence of the patients (non-French countries, French overseas territories, metropolitan France) or (b) more likely random in regions where diverse migration flows occurred.